Tinjauan ke atas tahap kesediaan pelajar terhadap kerjaya pendidik di politeknik : satu kajian kes di kalangan graduan Sarjana Pendidikan (Teknikal) di Kolej Universiti Teknologi Tun Hussein Onn, Batu Pahat - Shaari, Sheilani (2001)
This study entitled "An overview on the level of readiness of the students in pursuing teaching career in the polytechnics : a case study among the graduate students of the Masters in Education (Technical) ofKolej Universiti Teknologi Tun Hussein Onn, Batu Pahat." This is the only pre-service post graduate career training programme in technical and vocational education in the country. The design and scope of the curriculum of this programme was specifically design to train engineers and technologist to become teacher in technical and vocational education sector in polytechnics. Since, there were no formal evaluation or tracer studies being conducted for this programme. Therefore, this study intended to evaluate the successfulness ofKUiTTHO graduates in meeting the professional needs. The entire population of 86 graduate in the final semester participated as respondent of this sample. Feedbacks through questionnaires were analised for value of min, standard deviation and one way ANOT'A were calculated using Statistical Package.for Social Sc1e11ce (SPSS) software. The finding showed that there were strong relationship between the level of acquisition of knowledge and expertise towards the professional readiness in pursuing teaching careers in technical and vocational education sectors in polytechnics.